The Importance Of Proteins And Protein-Containing Medicinal Products In Medicine (Texas Journal of Medical Science, 2026)
This article analyzes the biological and physiological significance of proteins, their main functions in the human body, as well as protein-based drugs and their fields of application in medicine. Proteins are the principal structural components of every living cell and play an essential role in metabolism, immune defense, enzymatic processes, and the maintenance of cellular integrity. The article also provides a broad overview of pathological conditions associated with proteins and the medical need for protein substances in clinical practice. It serves to strengthen theoretical knowledge and foster clinical thinking among students studying in the field of medicine